The adjusted value chain model for the public science and technology organizations in line with the conditions of Vietna - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This research aims to introduce a new mode of operation based on Michael Porter’s model of value chain with some adjustments to the operational mode of public science and technology (S&T) organizations in Vietnam. The new mode of operations illustrates the relationships between activities within the research, business and production associated organizations and their approaches to create values. Besides, the model could be a basis for the managers to evaluate and provide decisive considerations to outsource for their partners some of these activities in the value chain. Code: 16120801